The conductivity and dielectric studies of solid polymer electrolytes based on poly (acrylamide-co-acrylic acid) doped with sodium iodide - Saminatha Kumaran, V.; Ng, H.M.; Ramesh, Subramaniam; Ramesh, Kasi; Vengadaesvaran, B.; Numan, Arshid (Springer Verlag (Germany), 2018)
Solid polymer electrolyte thin films based on polyacrylamide-co-acrylic acid (PAAC) doped with sodium iodide (NaI) with different ratios of polymer and salt added with fixed amount of additive of propylene carbonate (PC) were prepared by using solution casting method. The PC was added to the mixture of the solution to provide more flexibility to the polymer film by increasing the plasticity of the thin film membrane. The conductivity and dielectric studies were carried out on these thin films to understand the ion transport properties of the polymer electrolytes. The highest conductivity obtained was 1.88 × 10−5 S cm−1 for the 30% NaI salt-doped polymer electrolyte system at room temperature. The temperature-dependent conductivity agrees with Arrhenius relationship which shows that hopping mechanism of ions in the polymer matrix. The dielectric properties especially the loss tangent used to analyze the segmental relaxation of the polymer chain as more concentration of salt was incorporated. The electric modulus was studied to understand the electrical relaxation processes to overcome electrode polarization effect.